Probing pathways of adaptation with continuous evolution. Issue 14 (April 2019) - Zhong, Ziwei; Liu, Chang C.
Abstract: Directed evolution is a powerful strategy for studying the basic principles of adaptation, but difficulties in traditional methods limit the types of evolutionary questions that can be addressed. By enabling the rapid traversal of long mutational pathways with extensive experimental replication, continuous evolution systems promise to extend the reach of directed evolution in studying how biomolecules evolve.